Stockholm The Tale of the Unicorn Factory (Volume 6) - Zetterberg, Olof (European Investment Bank, 2019)
Once upon a time there was a city in a cold place a long way to the north. One day the city started to tell a story about itself. As the chapters unfolded, life in the city changed, and soon it didn't even seem so cold or far away any more. People listened to the story and realised that the city wasn't quite what they expected. They started to tell the story to each other about how the city had created a magical unicorn factory... Here's how Stockholm built a narrative for itself - and backed it up with urban development that was innovative and sustainable.